Jurnal Akuntansi & Investasi: Pengaruh Partisipasi Anggaran, Kejelasan Sasaran Anggaran, Pengendalian Akuntansi n Sistem Pelaporan terhdp Akuntabilitas Kinerja Instansi PemDa dgn Komitmen Organisas - Beny Arifin W (Akuntansi FE UMY, 2012)
This research is conducted to examine the effect of budget participation, budget goal clarity, accounting control and reporting system on performance accountability of government agencies with organizational commitment as a moderating variable. The sample in this study was taken with a purposive sample of non probability sampling that adjusted with certain criteria or considerations. The sample in this study are structural officials in Pekalongan Regency which amounted to 90 respondents.